Bridging the gap: enhancing career counseling services for Chinese students in Malaysian universities - Puad Mohd Kari, Dharatun Nissa; Ya, Zhong (Human Resources Management Academic Research Society (HRMARS), 2024)
The career development of Chinese international students in Malaysia is significantly influenced by their ability to access and engage with career counseling services. However, these services are often underutilized due to cultural, linguistic, and institutional barriers. This study explores the expectations, perceptions, and barriers experienced by Chinese students at Universiti Putra Malaysia regarding career counseling. Using a qualitative research design, in-depth interviews with eight students revealed that while they recognize the benefits of career counseling, significant challenges limit their access. Key barriers include cultural stigma associated with seeking help, language difficulties, and a lack of culturally tailored services. Participants expressed a need for more personalized and culturally relevant counseling, particularly through the availability of Mandarin-speaking counselors and resources that address their specific needs. The findings suggest that Malaysian universities can better support Chinese international students by adopting a more culturally sensitive approach, including enhanced outreach and tailored services. This study provides practical recommendations for improving the effectiveness of career counseling services, ultimately empowering Chinese students to achieve their academic and career goals in Malaysia.